926 nm laser operation in Nd:GdNbO4 crystal based on 4F3/2 → 4I9/2 transition. (May 2018) - Yan, Renpeng; Li, Xudong; Yao, Wenming; Shen, Yingjie; Zhou, Zhongxiang; Peng, Fang; Zhang, Qingli; Dou, Renqing; Gao, Jing
Highlights: An LD-pumped 926 nm laser with Nd:GdNbO4 is presented for the first time. Direct pumping is utilized to achieve efficient 926 nm laser output. The results show Nd:GdNbO4 is a promising candidate to generate 0.9 μm laser. Abstract: 926 nm laser operation in a Nd:GdNbO4 crystal based on quasi-three-level 4 F3/2  →  4 I9/2 transition is reported, for the first time to our best knowledge. An average output power of 393 mW at 926 nm under 879 nm LD pumping is obtained with a slope efficiency of 33.3% and an optical-to-optical efficiency of 26.0%. The slope efficiency with respect to absorbed pump power is estimated to be 47.7%. Comparison between output characters of 926 nm laser under direct and indirect pumping is conducted. The average output power at 926 nm under 808 nm LD pumping reaches 305 mW with an optical-to-optical efficiency of 16.1%.